A Review of Some of the Challenges and Obstacles to Implementation of General Principles of Article 44 of the Constitution: A Case Study of National Iranian Oil Refining and Distribution Company - Nader Mirzadeh Kohshahi; Mohmmad Rahman Gaeeni (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
In this article, regarding some of the obstacles and challenges of implementing the law, the implementation of Article 44 of the Constitution in the National Iranian Oil Refining and Distribution Company addresses the analysis of the outlines of these ambiguities and challenges. In analyzing this issue, there are several categories more than others: ambiguity in the basics and principles, the challenge in the public service, the conflict of assignments with the type of constitutional government, the confusion in the institution, the ownership of the ventures, the ambiguity about the employees employed in the corporations, the challenge of retirement, and the ambiguity in the rates of corporate governance and privileges. Each of these issues is individually dealt with analytically and within the scope of the research, including the sample the effects, consequences, and the manner of operation of the relevant institutions in order to resolve them based on the documents and approvals.